Analysis of Factors Affecting Dishonesty in Questionnaire Filling: A Phenomenological Approach to Undergraduate Education Respondents - Azfaruddin, Muhammad Farid; Lukman, Muhammad Ghiffari; Solichatun, Yulia; Rahayu, Iin Tri; Ridho, Ali (Proceedings Conference Psychology and Flourishing Humanity; Vol 1 No 1 (2024): Proceedings Conference on Psychology and Flourishing Humanity, 2025)
Responses that are inconsistent with expectations are referred to as Aberrant responses, Aberrant response behavior is a challenge in research because it can compromise data quality and encourage analysis errors. Thus, a deep understanding of the challenges and implications of Aberrant response in questionnaires is important in designing and analyzing questionnaire data. The purpose of the study is to find out what factors cause respondents not to fill out the questionnaire correctly and honestly, and how respondents think that when filling out the questionnaire can provide honest answers. The focus of this research is on the factors that cause respondents not to fill in honestly, and how to form a questionnaire so that respondents can fill in honestly. The method in this study is a qualitative approach with phenomenological methods, the subjects in this study amounted to 4 people with a Undergraduate (S1) educational background. The data collection method uses structured interviews. Data analysis techniques use interactive methods, namely data reduction, presenting data, making conclusions and virification. The results of this study indicate 1) Factors that caused respondents not to fill out the questionnaire correctly and honestly included. To maintain self-image, lack of motivation to participate in the study, fear of consequences, not understanding the questions or instructions in the questionnaire. 2). Respondents' opinions so that when filling out the questionnaire can provide honest answers are. Guarantee confidentiality, provide an understanding that there are no negative consequences when answering, and use questions that are easy to understand, clear instructions, and not too many items.